KETIDAKEFEKTIFAN KALIMAT DALAM RUBRIK â€œOPINIâ€ MAJALAH PENDAPA TAMANSISWA - Yulika Dwi Astuti; Mukhlish Mukhlish (CARAKA, 2017)
The purpose of this research is to describe ineffective sentences on the "Opinion" rubric of Pendapa Tamansiswa magazine. In the detail of purpose, this research is to describe (1) the ineffectiveness of words selection, (2) the ineffectiveness of sentences structure, and (3) the uncertainty of apply spelling words. Kind of this research is descriptive qualitative research. The data of this research is the ineffectiveness sentences in the "Opinion" rubric of Pendapa Tamansiswa magazine. The source data of this research is â€œOpinionâ€ rubric onÂ  Pendapa Tamansiswa magazine. In this research the source data from magazines that were published from 2005 until 2015. From eight Pendapa Tamansiswa magazines, there are eleven rubric opinions. The method of providing data is listening. The technique of provision data uses listening technique and note technique. The method to the analysis of data is agih method, while the analysis technique of data use the base technique for direct element., with other techniques like replace technique, expansion technique, return technique, and disappeared technique. The result this research is a description of ineffectiveness sentences in the â€œOpinionâ€ rubric of Pendapa Tamansiswa magazine. From 631 sentences that were analyzed, there are 263 sentences or several 41,68 % that not effective. There are ineffectiveness sentences. (1) The ineffectiveness of words selection as many as 59 sentences or 9,35 %, includes (a) the ineffectiveness of words selection and (b) the incompatibility words selection. (2) the ineffectiveness of sentence structure are 46 sentences or 7,29% includes (a) not the unity of ideas, (b) the blend sentence, (c) the waste of sentence, (d) not synchronous sentences, (e) not logically sentences. (3) Spelling inaccuracy several 132 sentences or 20,92% , includes (a) the improper use of letters, (b) the inaccurate of writing, (c) the imprecise use of punctuation, and (d) the inaccuracy of writing the absorption element. (4) The mixed effectiveness amount of 26 sentences or 4,12% , includes (a) the ineffectiveness of word choices and the ineffectiveness of sentence structure, (b) the ineffectiveness of word choices and inaccuracy of spellingÂ  amount, (c) the ineffectiveness of sentences structure and inaccuracy of spelling, and (d) the ineffectiveness of word choices and the ineffectiveness of sentences structure and inaccuracy of spelling.